Measuring self–compassion in the elderly - Hassan, Ayaat Mohamed; Hussein, Thuriayh Ali (Al-Adab Journal, 2021)
The current research aimed to measure self-compassion in the elderly. Self-compassion in the elderly is identified according to the gender variable, and the place of residence outside homes for the elderly and inside homes for the elderly. The current research sample reached (286) elderly people in Baghdad governorate, in a random way. Research tool: The Neff scale (2003) Arabization of Zarzis (2010) was adopted. And then the psychometric properties of the scale were extracted. The results of the research showed: The elderly have statistically significant self-compassion, the presence of statistically significant differences among the elderly outside the role, and there are no statistically significant differences according to the gender variable.